2002
DOI: 10.1093/jnci/94.16.1197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Proton Magnetic Resonance Spectroscopy in Characterizing Breast Lesions

Abstract: Proton magnetic resonance spectroscopy ((1)H MRS) of the breast has been proposed as an adjunct to the magnetic resonance imaging (MRI) examination to improve the specificity of distinguishing malignant breast tumors from benign breast tumors. In this review, we carry out a pooled analysis of the clinical breast (1)H MRS studies undertaken to date to determine the factors that influence the diagnostic performance of this method. In total, five studies of breast (1)H MRS from four independent centers around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
205
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(213 citation statements)
references
References 37 publications
5
205
1
2
Order By: Relevance
“…Diffusion-weighted MRI can be used to detect changes in the apparent diffusion coefficient (ADC) for tissue water associated with changes in tissue and intracellular structure (Zhao et al, 1996;Gallons et al, 1999;Ross et al, 2003;Moffat et al, 2005). Proton magnetic resonance spectroscopy (MRS) can be used to characterise breast lesions through differences in the ratio of fat and water signals (Chu et al, 1987;Sijens et al, 1988) or the intensity of signal from choline-containing compounds (Bradamante et al, 1988;Katz-Brull et al, 2002;Bolan et al, 2003;Jacobs et al, 2004;Jacobs et al, 2005). Both fat : water ratios (Jagannathan et al, 1998) and choline levels (Preul et al, 2000;Jagannathan et al, 2001;Schwarz et al, 2002;Meisamy et al, 2004) have also been used to monitor treatment-induced changes, and phosphorous MRS has been used to predict response using differences in the levels of phosphocholine or phosphomonoesters (Shukla-Dave et al, 2002a, b;Arias-Mendoza et al, 2004).…”
mentioning
confidence: 99%
“…Diffusion-weighted MRI can be used to detect changes in the apparent diffusion coefficient (ADC) for tissue water associated with changes in tissue and intracellular structure (Zhao et al, 1996;Gallons et al, 1999;Ross et al, 2003;Moffat et al, 2005). Proton magnetic resonance spectroscopy (MRS) can be used to characterise breast lesions through differences in the ratio of fat and water signals (Chu et al, 1987;Sijens et al, 1988) or the intensity of signal from choline-containing compounds (Bradamante et al, 1988;Katz-Brull et al, 2002;Bolan et al, 2003;Jacobs et al, 2004;Jacobs et al, 2005). Both fat : water ratios (Jagannathan et al, 1998) and choline levels (Preul et al, 2000;Jagannathan et al, 2001;Schwarz et al, 2002;Meisamy et al, 2004) have also been used to monitor treatment-induced changes, and phosphorous MRS has been used to predict response using differences in the levels of phosphocholine or phosphomonoesters (Shukla-Dave et al, 2002a, b;Arias-Mendoza et al, 2004).…”
mentioning
confidence: 99%
“…In vitro MRS of breast cell lines confirms that Cho levels increase with progression from normal to immortalized to oncogene-transformed to tumor-derived cells [31]. Analysis of early pooled clinical experience with in vivo 1 H MRS yielded a sensitivity and specificity for detection of breast cancer of 83% and 85%, respectively, with near 100% for both in a subgroup of young women [32]. A reduction or disappearance of the Cho signal has been associated with response to neoadjuvant chemotherapy of locally advanced breast cancer [33].…”
Section: Introductionmentioning
confidence: 93%
“…Normal tissue, and many firoadenomas, should not exceed a Cho concentration of 1 mmol.kg -1 , so a concentration higher than this value is suspicious for malignancy. However, this may not be the case under all circumstances; for instance, it has been reported that Cho and lactose signals (~3.8 ppm) can be observed in women who are lactating (27,37,39).…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…Various factors, as listed below, should be kept in mind when evaluating spectra from breast lesions (27,31,32,37,39): v Lesion size: Since the signal-to-noise ratio (SNR) of a spectrum depends linearly on the voxel size (amongst other factors), smaller lesions will be less likely to show detectable tCho signal than larger ones. Limitation of lesions is 2 cm 3 or larger at 1.5 T. v SNR: It should also be kept in mind that, under high SNR conditions, it is possible to detect tCho signal from normal fibroglandular tissue.…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%